2000
DOI: 10.1212/wnl.54.9.1872
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea: A study by simultaneous polysomnography and ultrasonic imaging

Abstract: Obstructive sleep apnea (OSA) is associated with major morbidity and daytime somnolence. 1 Location of the obstruction cannot be determined by polysomnography, thereby contributing to variance in cure rates for surgical procedures such as uvulopalatopharyngoplasty (UPPP). 2,3 There is no clinically accepted, comfortable, and noninvasive method for visualizing the airway during sleep. Ultrasonic imaging of the airway is an established method used in the evaluation of swallowing. 4,5 It is a dynamic, safe method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Using a commercial ultrasound system and PSG for simultaneous recording in patients with OSA, Siegel et al . demonstrated a positive relationship between an ultrasonic event and the obstructive respiratory event, which was detected in the PSG (Siegel et al ., ). They defined the ultrasonic event as a posterior or inferior displacement of the tongue base toward the hypopharyngeal airway at the occurrence of and during each subsequent apnea.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using a commercial ultrasound system and PSG for simultaneous recording in patients with OSA, Siegel et al . demonstrated a positive relationship between an ultrasonic event and the obstructive respiratory event, which was detected in the PSG (Siegel et al ., ). They defined the ultrasonic event as a posterior or inferior displacement of the tongue base toward the hypopharyngeal airway at the occurrence of and during each subsequent apnea.…”
Section: Discussionmentioning
confidence: 97%
“…Automatic quantification of the differences among tongue contours obtained through ultrasound imaging has been proposed as a reliable method for the analysis of tongue positions during the production of various speech patterns (Lancia et al, 2015). Using a commercial ultrasound system and PSG for simultaneous recording in patients with OSA, Siegel et al demonstrated a positive relationship between an ultrasonic event and the obstructive respiratory event, which was detected in the PSG (Siegel et al, 2000). They defined the ultrasonic event as a posterior or inferior displacement of the tongue base toward the hypopharyngeal airway at the occurrence of and during each subsequent apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Full-night PSG (Somnologica 3.2; Embla, Denver, Colorado) was performed in the sleep center laboratory. The patients were divided into 4 groups according to the apneahypopnea index (AHI): normal and/or primary snoring (AHI \5), mild OSA (AHI = 5-15), moderate OSA (AHI = [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and severe OSA (AHI .30). The minimum oxygen saturation (MOS) value was recorded as a percentage.…”
Section: Methodsmentioning
confidence: 99%
“…6 In patients with sleep apnoea, upper airway ultrasonography has been used to visualise approximation of the tongue base posteriorly and inferiorly towards the hypopharynx to cause airway obstruction. 10,11 Pharyngeal or laryngeal pathology, such as tumours, abscesses or epiglottitis which may have a significant effect during airway management, are detected by the use of US scan.…”
Section: Predicting Difficult Intubationmentioning
confidence: 99%